Influence The Use of Blind Van Type Electric Cars Operational Energy Costs and Costs Maintenance Vehicle through Efficiency Cost Operations at PT. Dapensi Dwikarya - Agus Purnomo; Egana Dwi Saparingga; Melia Eka Lestiani; Purnomo, Agus (RADJA PUBLIKA, 2026)
The transition toward electric vehicles has encouraged logistics companies to empirically evaluate operational cost efficiency as part of sustainable transportation strategies. This study aims to analyze the effect of using electric blind vans on energy operational costs and vehicle maintenance costs through operational cost efficiency at PT. Dapensi Dwikarya, a logistics company operating in Indonesia. This research employs a quantitative explanatory approach using a survey method to examine the causal relationships among variables. Data were collected through structured questionnaires measured on a seven-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The analysis involves four main constructs: the use of electric blind vans, operational cost efficiency, energy operational costs, and vehicle maintenance costs. The results indicate that the use of electric blind vans has a positive and significant effect on operational cost efficiency. Furthermore, operational cost efficiency significantly affects both energy operational costs and vehicle maintenance costs. The findings also show that operational cost efficiency mediates the relationship between the use of electric blind vans and operational costs. Specifically, operational cost efficiency partially mediates the effect of electric blind van usage on energy operational costs and fully mediates its effect on vehicle maintenance costs. These results suggest that the economic benefits of adopting electric vehicles in logistics operations depend not only on vehicle technology but also on effective operational cost management to achieve long-term cost efficiency